2015
DOI: 10.1155/2015/958217
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Oil Containingα-Linolenic Acid Ester of Plant Sterol Improved Atherosclerosis in ApoE Deficient Mice

Abstract: Plant sterols (PS) have potential preventive function in atherosclerosis due to their cholesterol-lowering ability. Dietary α-linolenic acid in flaxseed oil is associated with a reduction in cardiovascular events through its hypolipidemic and anti-inflammation properties. This study was designed to evaluate the effects of flaxseed oil containing α-linolenic acid ester of PS (ALA-PS) on atherosclerosis and investigate the underlying mechanisms. C57BL/6 mice were administered a regular diet and apoE knockout (ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
1
26
0
2
Order By: Relevance
“…Results of various research studies have shown that the suppression of atherosclerosis is associated with reduced levels of serum lipids and antioxidant activity. A recent study hat was designed to evaluate the effects of flaxseed oil containing α-linolenic acid ester of plant sterols (ALA-PS) demonstrated that ALA-PS flaxseed oil synergistically interacted in atherosclerosis ameliorating as well as in optimizing overall lipid levels, contracting inflammation, and lowering oxidative stress [ 69 ]. Another animal study suggested that ingestion of oxidized flaxseed oil increases hepatic plasma malondialdehyde (MDA) concentration and is potentially pro-atherogenic.…”
Section: Resultsmentioning
confidence: 99%
“…Results of various research studies have shown that the suppression of atherosclerosis is associated with reduced levels of serum lipids and antioxidant activity. A recent study hat was designed to evaluate the effects of flaxseed oil containing α-linolenic acid ester of plant sterols (ALA-PS) demonstrated that ALA-PS flaxseed oil synergistically interacted in atherosclerosis ameliorating as well as in optimizing overall lipid levels, contracting inflammation, and lowering oxidative stress [ 69 ]. Another animal study suggested that ingestion of oxidized flaxseed oil increases hepatic plasma malondialdehyde (MDA) concentration and is potentially pro-atherogenic.…”
Section: Resultsmentioning
confidence: 99%
“…The latest study setup by Wang et al demonstrated that dietary ALA-rich flaxseed oil prevented alcoholic hepatic steatosis via ameliorating lipid homeostasis at the adipose tissue-liver axis in mice [ 26 ]. Meanwhile, it has been well established that increased consumption of ALA was associated with improvements in the level of TG and gene expression involved in fatty acid metabolism [ 27 , 28 ]. Consistent with previous research, in this work, we found that intervention of flaxseed oil decreased TG and TC in serum and liver, which indicated that supplement of flaxseed oil offered a strategy for optimizing lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment resulted in proliferation of endothelial cells and new vascular channel formation in the liver and between the cardiac muscle fibers. A study evaluating the effects of flaxseed oil demonstrated its efficacy in ameliorating atherosclerosis, optimizing overall lipid levels, and decreasing oxidative stress and inflammation [56]. A study in mice showed that fresh flaxseed oil can suppress hypercholesterolemic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%